2016
DOI: 10.1371/journal.pntd.0004867
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in District-Level Transmission of Ebola Virus Disease during the 2013-2015 Epidemic in West Africa

Abstract: The Ebola virus disease (EVD) epidemic in West Africa in 2013–2015 spread heterogeneously across the three hardest-hit countries Guinea, Liberia and Sierra Leone and the estimation of national transmission of EVD provides little information about local dynamics. To investigate district-level transmissibility of EVD, we applied a statistical modelling approach to estimate the basic reproduction number (R0) for each affected district and each country using weekly incident case numbers. We estimated growth rates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Additionally, virus transmission is influenced by socio-economic and behavioral factors including the health care response, society perceptions, religious practices, population density, and/ or infrastructure (13,18). Concordantly, R 0 s determined in different districts of Guinea, Liberia, and Sierra Leone during the West African Ebola virus epidemic ranged from 0.36 to 3.37 (19). High reproductive numbers (≥4) are typically observed at the beginning of Ebolavirus outbreaks, prior to the implementation of control measures (2023).…”
Section: Resultsmentioning
confidence: 86%
“…Additionally, virus transmission is influenced by socio-economic and behavioral factors including the health care response, society perceptions, religious practices, population density, and/ or infrastructure (13,18). Concordantly, R 0 s determined in different districts of Guinea, Liberia, and Sierra Leone during the West African Ebola virus epidemic ranged from 0.36 to 3.37 (19). High reproductive numbers (≥4) are typically observed at the beginning of Ebolavirus outbreaks, prior to the implementation of control measures (2023).…”
Section: Resultsmentioning
confidence: 86%
“…Additionally, virus transmission is influenced by socioeconomic and behavioral factors including the health-care response, society perceptions, religious practices, population density, and/or infrastructure ( 22 , 23 ). Concordantly, R 0 s that were determined by the same methodology in different districts of Guinea, Liberia, and Sierra Leone during the West African Ebola virus epidemic ranged from 0.36 to 3.37 ( 24 ). Three studies directly compared the Ebola virus outbreak in Kikwit (1995, DR Congo) and the Sudan virus outbreak in Gulu (2000/2001, Uganda) ( 25 27 ), but did not reveal fundamental differences between the R 0 s of the viruses (Data Sheets S1 and S2 in Supplementary Material).…”
Section: Resultsmentioning
confidence: 87%
“…We performed an analysis of the Ebolavirus vaccine requirements to achieve the V c needed for prophylactic mass vaccination programs. A number of studies suggested that Ebolavirus transmission can occur with R 0 values of 3, 4, or even higher, in particular during early outbreak stages (prior to the implementation of control measures) and/or as consequence of superspreading events ( 23 , 24 , 28 36 ). Therefore, a prophylactic vaccination program should establish herd immunity against Ebolaviruses that spread at such levels.…”
Section: Discussionmentioning
confidence: 99%
“…This filtered ensemble is then used to generate projections of the eventual outcome of the outbreak. 14 To model vaccination coverage with respect to total transmission (unreported and reported), we multiplied the estimate of vaccine effectiveness by low and high estimates of reported cases. In a ring vaccination study at the end of the West Africa outbreak, the overall estimated rVSV-vectored vaccine efficacy was 100% and vaccine effectiveness was 64.6% in protecting all contacts and contacts of contacts from EVD in the randomized clusters, including unvaccinated cluster members.…”
Section: Stochastic Branching Process Modelmentioning
confidence: 99%